Chlorogenic Acid Inhibits BAFF Expression in Collagen-Induced Arthritis and Human Synoviocyte MH7A Cells by Modulating the Activation of the NF-κB Signaling Pathway - Xiaohong Fu; Xilin Lyu; Han Liu; Dan Zhong; Zhizhen Xu; Fengtian He; Gang Huang (Journal of Immunology Research)
B cell activating factor (BAFF), a member of the tumor necrosis factor (TNF) family, plays a critical role in the pathogenesis and progression of rheumatoid arthritis (RA). Chlorogenic acid (CGA) is a phenolic compound and exerts antiarthritic activities in arthritis. However, it is not clear whether the anti-inflammatory property of CGA is associated with the regulation of BAFF expression. In this study, we found that treatment of the collagen-induced arthritis (CIA) mice with CGA significantly attenuated arthritis progression and markedly inhibited BAFF production in serum as well as the production of serum TNF-α. Furthermore, CGA inhibits TNF-α-induced BAFF expression in a dose-dependent manner and apoptosis in MH7A cells. Mechanistically, we found the DNA-binding site for the transcription factor NF-κB in the BAFF promoter region is required for this regulation. Moreover, CGA reduces the DNA-binding activity of NF-κB to the BAFF promoter region and suppresses BAFF expression through the NF-κB pathway in TNF-α-stimulated MH7A cells. These results suggest that CGA may serve as a novel therapeutic agent for the treatment of RA by targeting BAFF.